2006
DOI: 10.1523/jneurosci.0860-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Signatures of Cellular Plasticity in Mice Lacking the α1 Subunit of GABAAReceptors

Abstract: GABA A receptors mediate the majority of inhibitory neurotransmission in the CNS. Genetic deletion of the ␣1 subunit of GABA A receptors results in a loss of ␣1-mediated fast inhibitory currents and a marked reduction in density of GABA A receptors. A grossly normal phenotype of ␣1-deficient mice suggests the presence of neuronal adaptation to these drastic changes at the GABA synapse. We used cDNA microarrays to identify transcriptional fingerprints of cellular plasticity in response to altered GABAergic inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 69 publications
(102 reference statements)
3
49
0
Order By: Relevance
“…Although compensatory changes to the expression levels of other ␤ subunits might occur after removing the ␤2 subunit (Ponomarev et al, 2006), it seems unlikely that ␤1 subunit expression is increased because its expression is at best minimal in CGCs (Laurie et al, 1992;Pirker et al, 2000), which we confirmed in our ␤2 appear to be modulated by ␣-CaMK-II. This contrasts with the lack of modulation by ␣-CaMK-II of recombinant ␣1␤2␥2S receptors expressed in NG108-15 cells (Houston and Smart, 2006), which implies that the neuronal inhibitory synaptic environment is vitally important for supporting ␣-CaMK-II modulation of GABA A receptor isoforms.…”
Section: Discussionsupporting
confidence: 59%
“…Although compensatory changes to the expression levels of other ␤ subunits might occur after removing the ␤2 subunit (Ponomarev et al, 2006), it seems unlikely that ␤1 subunit expression is increased because its expression is at best minimal in CGCs (Laurie et al, 1992;Pirker et al, 2000), which we confirmed in our ␤2 appear to be modulated by ␣-CaMK-II. This contrasts with the lack of modulation by ␣-CaMK-II of recombinant ␣1␤2␥2S receptors expressed in NG108-15 cells (Houston and Smart, 2006), which implies that the neuronal inhibitory synaptic environment is vitally important for supporting ␣-CaMK-II modulation of GABA A receptor isoforms.…”
Section: Discussionsupporting
confidence: 59%
“…66 Furthermore, a targeted deletion of the GABA A receptor a1 subunit gene in mice resulted in altered cortical expression of other GABA A receptor subunits, such as increased a2 and decreased g2 protein levels, as well as decreased levels of SST mRNA. 67,68 Together, these findings suggest that the deficit in a1 subunit expression could be an upstream event to other GABA-related gene expression changes in the DLPFC of subjects with schizophrenia.…”
Section: Discussionmentioning
confidence: 85%
“…One of the problems in interpretation of results obtained with knockout mice is whether compensatory changes in expression of other genes occur as a result of deletion of particular gene (Ponomarev et al, 2006). Although this issue…”
Section: Discussionmentioning
confidence: 99%